Dosimetric feasibility of hippocampal avoidance whole brain radiotherapy with an MRI‐guided linear accelerator. Issue 6 (28th March 2022) - Graham, Jasmine A.; Redler, Gage; Delozier, Kirby B.; Yu, Hsiang‐Hsuan Michael; Oliver, Daniel E.; Rosenberg, Stephen A.
Abstract: Purpose/Objective(s): Whole brain radiotherapy with hippocampal avoidance (HA‐WBRT) is a technique utilized to treat metastatic brain disease while preserving memory and neurocognitive function. We hypothesized that the treatment planning and delivery of HA‐WBRT plans is feasible with an MRI‐guided linear accelerator (linac) and compared plan results with clinical non‐MRI‐guided C‐Arm linac plans. Materials/Methods: Twelve HA‐WBRT patients treated on a non‐MRI‐guided C‐Arm linac were selected for retrospective analysis. Treatment plans were developed using a 0.35T MRI‐guided linac system for comparison to clinical plans. Treatment planning goals were defined as provided in the Phase II Trial NRG CC001. MRI‐guided radiotherapy (MRgRT) treatment plans were developed by a dosimetrist and compared with clinical plans. quality assurance (QA) plans were generated and delivered on the MRI‐guided linac to a cylindrical diode detector array. Planning target volume (PTV) coverage was normalized to ∼95% to provide a control point for comparison of dose to the organs at risk. Results: MRgRT plans were deliverable and met all clinical goals. Mean values demonstrated that the clinical plans were less heterogeneous than MRgRT plans with mean PTV V37.5 Gy of 0.00% and 0.03% ( p = 0.013), respectively. Average hippocampi maximum doses were 14.19 ± 1.29 Gy and 15.00 ± 1.51 Gy, respectively. The gamma analysis comparing planned and measured doses resulted in a mean of 99.9% ± 0.12% of passing points (3%/2mm criteria). MRgRT plans had an average of 38.33 beams with average total delivery time and beam‐on time of 13.7 (11.2–17.5) min and 4.1 (3.2–5.4) min, respectively. Clinical plan delivery times ranged from 3 to 7 min depending on the number of noncoplanar arcs. Planning time between the clinical and MRgRT plans was comparable. Conclusion: This study demonstrates that HA‐WBRT can be treated using an MRI‐guided linear accelerator with comparable treatment plan quality and delivery accuracy.